2023
DOI: 10.1097/sla.0000000000006049
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation (LDLT) for Hepatocellular Carcinoma (HCC) within and Outside Traditional Selection Criteria

Abstract: Objective: We evaluated long-term oncologic outcomes of patients post-LDLT within and outside standard transplant selection criteria and the added value of the incorporation of the New York-California (NYCA) score. Summary Background Data: LDLT offers an opportunity to decrease the liver transplant waitlist, reduce waitlist mortality and expand selection criteria for patients with HCC. Methods: Primary adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…There have been further adjustments to the classification for HCC, which have not been discussed further here [ 28 , 43 , 49 , 50 ]. These include, for example, the modification of the TNM criteria for HCC from Pittsburgh [ 51 ] and the Hangzhou criteria [ 49 ] for LT at HCC.…”
Section: Discussionmentioning
confidence: 99%
“…There have been further adjustments to the classification for HCC, which have not been discussed further here [ 28 , 43 , 49 , 50 ]. These include, for example, the modification of the TNM criteria for HCC from Pittsburgh [ 51 ] and the Hangzhou criteria [ 49 ] for LT at HCC.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown for which patients living donation is a good alternative to deceased organ donation. Living donation can be considered especially in the combination of decompensated underlying disease and a low MELD score or for patients with malignant disease without the option for exceptional MELD [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing recipients who met Milan and UCSF criteria found no difference in survival rates following LT. 10 A multicenter study demonstrated that the 10-year survival rates after LDLT in patients within Milan and UCSF criteria were 64.1% and 69.4%, respectively. 11 In the Asian perspective, overall survival rates ranged from 80% to 85.2% after LT with more expanded selection criteria. 12 According to the present study, the overall survival rates at 1, 5, and 10 years were consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%